Land for peace? Israel-Palestine through the lens of game theory - Amal Ahmad (University of Massachusetts, Department of Economics, 2021)
Why have Israel and the Palestinians failed to implement a "land for peace" solution, along the lines of the Oslo Accords? This paper studies the application of game theory to this question. I show that existing models of the conflict largely rely on unrealistic assumptions about what the main actors are trying to achieve. Specifically, they assume that Israel is strategically interested in withdrawing from the occupied territories pending resolvable security concerns but that it is obstructed from doing so by violent Palestinians with other objectives. I use historical analysis along with bargaining theory to shed doubt on this assumption, and to argue that the persistence of conflict has been aligned with, not contrary to, the interests of the militarily powerful party, Israel.
Keywords: D74; F51; 330; Israel-Palestine; international conicts; strategic behavior